Iron-containing Water of the Yamal-Nenets Autonomous District - BESHENTSEV, Vladimir A.; ABDRASHITOVA, Rimma N.; KOVYATKINA, Lyubov A.; SALNIKOVA, Yuliya I.; SABANINA, Irina G.; LAZUTIN, Nikolay K. (Journal of Environmental Management and Tourism, 2018)
Factors of groundwater formation in the Yamal-Nenets Autonomous District predetermined its specific composition, characterized by low (ultra-fresh) mineralization, rarely exceeding 100 mg/dm3, reduced concentrations of the main macrocomponents and high concentrations of iron and manganese. Almost everywhere in the region under consideration, iron content exceeds the MAC by sanitary rules and rates 2.1.4.1074-01 "Drinking water", sometimes reaching tens of mg/dm3. On average, its values lie in the range from 1.4 to 6.5 mg/dm3 (at a rate of 0.3 mg/dm3). The presence of marshes and an increased content of organic substances in the aquifers of the Quaternary and Cretaceous-Paleogene deposits of the basin in the ice-humid and humid macrozones contribute to the creation of a primarily acidic reducing environment favorable for the migration of iron, manganese and other elements. The purpose of this study was to construct a mathematical model describing the dependence of the distribution of iron forms in the groundwater of the region on the pH which falls into the interval 5.5 - 7.5. These calculations eventually allowed us to recommend the most effective water treatment measures.